Assessing plasma activated water irrigation effects on tomato seedlings - Aceto, Domenico; Rotondo, Palma Rosa; Porfido, Carlo; Bottiglione, Benedetta; Paciolla, Costantino; Terzano, Roberto; Minafra, Angelantonio; Ambrico, Marianna; Dilecce, Giorgio; Leoni, Beniamino; De Miccolis Angelini, Rita Milvia; Ambrico, Paolo Francesco (Frontiers in Physics, 2024)
Introduction: The study investigates the potential of Plasma Activated Water (PAW) as an innovative irrigation medium to enhance growth and defense responses in tomato seedlings. It explores PAW’s utility in both healthy seedlings and those inoculated with Tomato mottle mosaic virus (ToMMV). Methods: PAW, produced through a dielectric barrier volume discharge, serves as a chemical-free alternative to traditional fertilizers. Tomato seedlings were irrigated with PAW or control solutions. The study employs biometric measurements to assess growth and biochemical analysis to evaluate antioxidant levels and pigments. Gene expression analysis was conducted to evaluate the plant response, while the distribution of macro and micronutrients was assessed through micro X-ray fluorescence. Results and discussion: Results indicate that PAW-irrigated seedlings exhibit significant growth enhancement compared to those receiving conventional fertilization. Increased levels of antioxidant molecules and pigments suggest improved photosynthetic activity and stress tolerance. Gene expression analysis shows up-regulation of defense genes in PAW-treated plants post-viral infection. The up-regulation of defense genes and the restoration of mineral nutrient distribution in PAW-treated, virus-infected plants highlight PAW’s role in enhancing plant resilience against pathogens and mitigating nutrient deficiencies. These findings emphasize PAW’s potential as a sustainable agricultural solution, promoting plant growth, enhancing defense mechanisms, and reducing biotic stress due to virus infections.